6t-17-4t=10

Simple and best practice solution for 6t-17-4t=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-17-4t=10 equation:


Simplifying
6t + -17 + -4t = 10

Reorder the terms:
-17 + 6t + -4t = 10

Combine like terms: 6t + -4t = 2t
-17 + 2t = 10

Solving
-17 + 2t = 10

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 2t = 10 + 17

Combine like terms: -17 + 17 = 0
0 + 2t = 10 + 17
2t = 10 + 17

Combine like terms: 10 + 17 = 27
2t = 27

Divide each side by '2'.
t = 13.5

Simplifying
t = 13.5

See similar equations:

| 4y+32=11+6y | | 6x+10=20x-8 | | 4*(n+1)=32 | | 3(8+8x)+6= | | 4k-(7+k)=-(8k+7) | | -x-14=6+3x | | 3m=3m+5 | | 6x+4(6x-12)=132 | | -21=-7/5v | | 4z+9=8 | | -3x+23=5 | | 5p+5(-5-3p)= | | 2x+2x-14=x+9+x+2+x-7 | | 9(4+v)+32v=11v | | 1/4(8x-12)-20 | | 10u+20=170 | | 2.3(x+1.4)=-99.66 | | 3600=(1/x) | | -4-x=8+3x | | 2x+6(3x-6)=64 | | x=1.2/40.8 | | 1/2(2x-2) | | 2x+3(5x+17)=170 | | 1.2=40.8 | | y=(.5x-3)x(.5x-3)x(.5x-3) | | 2x-6=-x+9 | | y=43-3/4 | | x/1.2=40.8 | | -4(5-4y)=9y+50 | | 5x+2(4x+4)=86 | | 3x-4=4x-5 | | x=3/5/1/4 |

Equations solver categories